Good Financial Bookkeeping Training for Village Women Farmers Group “KWT” in Indonesia: Pengabdian - Rabiyatul Jasiyah; Siti Aisyah; Rieneke Ryke Kalalo; Andi Asrijal; Retno Dewi Wijiastuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This training was conducted by the author on a number of Women Farmers Groups, namely the Mawar Kolaka Women Farmers Group. This training was conducted by the author for ten days with a number of materials that the author believes can make each Women Farmers Group able to record the finances of the Women Farmers Group well. The author believes that the five materials that the author trained the administrators of the Women Farmers Group who are the objects in this article can make the financial system, both bookkeeping of income, expenses, and so on, better. The author also realizes that understanding the material that the author conveys is not as easy as turning the palm of the hand. However, the author has tried as much as possible to convey the material simply and understandably. The author hopes that the improvement in the financial bookkeeping of each Women Farmers Group that is the object of this article can be better in the future